2016
DOI: 10.1016/j.seares.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Particles transformation in estuaries: Fe, Mn and REE signatures through the Loire Estuary

Abstract: During their transfer across estuaries, particles endure numerous cycles of deposition-resuspension accompanied by several redox oscillations. These oscillations are likely to modify the particles content of redox sensitive metals such as Fe, Mn and two rare earth elements (REE): Ce and Eu. The present paper focuses on the fate of particles originating from the Loire Estuary by the study of chemical composition changes of both total and ascorbate-extracted phases. Transformations of particles buried in the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 72 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The distribution of REEs in estuarine sediments is influenced by various early diagenetic processes, particularly co‐precipitation into Fe‐Mn oxides/oxyhydroxides, redox conditions in the water column, the composition of terrigenous sources, and anthropogenic inputs (Brito, Prego et al., 2018). Several authors have studied the geochemical cycling of the REEs in estuaries, which can be used as geochemical indicators associated with the origin of the sediments (Babu et al., 2021; Censi et al., 2005; de Chanvalon et al., 2016; de Freitas et al., 2021; Hannigan et al., 2010; Merschel et al., 2017; Munksgaard et al., 2003; Prego et al., 2009; Silva‐Filho et al., 2011). Bayon et al.…”
Section: Environmental Distribution and Controlling Processes—element...mentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of REEs in estuarine sediments is influenced by various early diagenetic processes, particularly co‐precipitation into Fe‐Mn oxides/oxyhydroxides, redox conditions in the water column, the composition of terrigenous sources, and anthropogenic inputs (Brito, Prego et al., 2018). Several authors have studied the geochemical cycling of the REEs in estuaries, which can be used as geochemical indicators associated with the origin of the sediments (Babu et al., 2021; Censi et al., 2005; de Chanvalon et al., 2016; de Freitas et al., 2021; Hannigan et al., 2010; Merschel et al., 2017; Munksgaard et al., 2003; Prego et al., 2009; Silva‐Filho et al., 2011). Bayon et al.…”
Section: Environmental Distribution and Controlling Processes—element...mentioning
confidence: 99%
“…The distribution of REEs in estuarine sediments is influenced by various early diagenetic processes, particularly co-precipitation into Fe-Mn oxides/oxyhydroxides, redox conditions in the water column, the composition of terrigenous sources, and anthropogenic inputs (Brito, Prego et al, 2018). Several authors have studied the geochemical cycling of the REEs in estuaries, which can be used as geochemical indicators associated with the origin of the sediments (Babu et al, 2021;Censi et al, 2005;de Chanvalon et al, 2016;de Freitas et al, 2021;Hannigan et al, 2010;Merschel et al, 2017;Munksgaard et al, 2003;Prego et al, 2009;Silva-Filho et al, 2011). Bayon et al (2015) confirmed earlier assumptions that river sediments do not generally exhibit significant grainsize dependent Nd isotopic variability, although, a subtle decoupling of Nd isotopes between clays and silts was identified in a few major river systems, suggesting that preferential weathering of volcanic and/or sedimentary rocks relative to more resistant lithologies may occur in river basins, possibly leading locally to Nd isotopic decoupling between different size fractions.…”
Section: Estuariesmentioning
confidence: 99%
“…Another difference between these studies is the absence of macrophytes at the studied stations of the Brillantes mudflat. Finally the size of the catchment area of Loire provides an important flux of suspended particles rich in metallic oxides that will once settled in the mudflat generate a thick layer of sediment where the iron cycle dominates diagenetic processes acting as an efficient "iron curtain" that maintains free-sulphide between 5 to 10 cm depth (Thibault de Chanvalon et al, 2016bChanvalon et al, , 2016a to be out of reach for CB. These combined conditions are not favourable to CB development (Malkin et al, 2014(Malkin et al, , 2017.…”
Section: Impact Of Cable Bacteria On Living Foraminiferamentioning
confidence: 99%
“…Hence, the linear relationship between EF (Eq. 34) suggests a mixing of a terrigeneous endmember with an endogenous Mn oxo-hydroxide precipitate endmember, probably produced during the reoxidation of efflux of dissolved Mn, coming from the reducing part of the sediment (Thibault de Chanvalon et al 2016). This mechanism represents a credible opportunity for As, Ba and Co to co-precipitate in the newly formed Mn oxyhydroxide.…”
Section: Effect Of Geochemical Variablesmentioning
confidence: 99%